Letters, fictions, lives : Henry James and William Dean Howells - James, Henry, 1843-1916 (Oxford University Press, 1997)
This volume attempts to determine the early influence shared between William Dean Howells and Henry James by reconstructing and evaluating documentary evidence of their literary cross-fertilization. The 151 letters included represent each writer's most significant criticism of the other.
Keywords: James, Henry, -- 1843-1916 -- Correspondence.; Howells, William Dean, -- 1837-1920 -- Correspondence.; Howells, William Dean, -- 1837-1920; James, Henry, -- 1843-1916; Authors, American -- 19th century -- Correspondence.; Authors, American -- 20th century -- Correspondence.; Novelists, American -- 19th century -- Correspondence.; Novelists, American -- 20th century -- Correspondence.; Critics -- United States -- Correspondence.; Fiction -- Authorship.; Écrivains américains -- 19e siècle -- Correspondance.; Écrivains américains -- 20e siècle -- Correspondance.; Romanciers américains -- 19e siècle -- Correspondance.; Romanciers américains -- 20e siècle -- Correspondance.; Critiques -- États-Unis -- Correspondance.; Roman -- Art d'écrire.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; LITERARY CRITICISM -- American -- General.; Authors, American; Critics; Fiction -- Authorship; Novelists, American; United States; 1800-1999; Electronic book.; Biography; personal correspondence.; Biographies; Personal correspondence; Biographies.; Personal correspondence.; Correspondance privée.